The World Saffron and Crocus collection: strategies for establishment, management, characterisation and utilisation - Fernandez, Jose-Antonio; Santana, Omar; Guardiola, Jose-Luis; Molina, Rosa-Victoria; Heslop-Harrison, Pat; Borbely, George; Branca, Ferdinando; Argento, Sergio; Maloupa, Eleni; Talou, Thierry; Thiercelin, Jean-Marie; Gasimov, Khalil; et al. (Springer Science and Business Media LLC, 2010)
Many of the results presented in this paper are an outcome of the project "Genetic Resources of Saffron and Allies" (CROCUSBANK, http://www.crocusbank.org). This action receives financial support from the European Commission, Directorate General for Agriculture and Rural Development, under the Council Regulation (EC) No. 870/2004 establishing a Community Programme on the conservation, characterisation, collection, and utilisation of genetic resources in Agriculture (018 AGRI GEN RES ACTION). In addition some of the activities presented took a long period of time and have been partially supported by the following projects or actions: RFP-1 (Consejeria de Agricultura, JCCM, Spain), 05-172/IA-35 (Consejeria de Agricultura, JCCM, Spain), PAI09-0021-0413 and PBI09-0025-1537 (Consejeria de Educacion y Ciencia, JCCM, Spain), RF2008-0012-C03 (Instituto Nacional de Investigacion y Tecnologia Agraria y Alimentaria, MEC, Spain), RF2004-0032-C03 (Instituto Nacional de Investigacion y Tecnologia Agraria y Alimentaria, MEC, Spain). Special thanks to the following donor's institutions: Regulatory Council for the "La Mancha Saffron" designation of origin (DOP, La Mancha, Spain); The Royal Veterinary and Agricultural University (Denmark); Asociacion de Naturalistas del Sureste (ANSE, Spain); Centro de Investigacion y Tecnologia Agroalimentaria de Aragon (CITA, Spain); MTS Schipper & Elberse (Holland); Botanic Garden Utrecht University (The Netherlands); National Botanic Garden of Belgium (Belgium); Jardin Alpin du Lautaret (France); Frega S. R. L. (Argentina); Conservatoire et Jardin Botaniques de la Ville Geneve (Switzerland); Herbario Sant (Spain); Conservatoire Botanique National de Brest (France); Jardin des Plantes Medicinales et Aromatiques (France); Baby Brand Saffron (India); Azienda Agricola di Di Marco Amalia (Italy); Azienda Agricola IL Vecchio Maneggio (Italy); New Zealand Institute for Crop and Food Research (New Zealand); Ljubljana University Botanic Garden (Slovenia) and the Afghanistan Government. We thank very much the traditional saffron growers of different countries (Spain, France, Greece, Italy, Iran, Morocco, etc.), associations, companies, researchers, forest rangers and all the people who have contributed with materials included in the collection (for more detailed information see the website www.crocusbank.org).

[EN] Since 2007, the European Commission AGRI GEN RES 018 "CROCUSBANK" action has permitted the creation of the alleged World Saffron and Crocus Collection (WSCC), a unique collection which contains a representation of the genetic variability present in saffron crop and wild relatives at global scale. At present the germplasm collection, housed at the Bank of Plant Germplasm of Cuenca (BGV-CU, Spain), consists of 572 preserved accessions representing 47 different Crocus species (including saffron Crocus) and is expected to increase up to more than 600 accessions by the end of CROCUSBANK action (May 2011). The preserved biodiversity of saffron (Crocus sativus L.) covers a wide range of the genetic variability of the crop and currently consists of 220 accessions from 15 countries: 169 of these come from European cultivation countries, 18 from commercial areas in non EU countries, 26 from regions of minimal or relict production and/or from abandoned fields and 7 from commercial nurseries. The non-saffron Crocus collection currently comprises 352 accessions: 179 collected from the wild in 12 countries of natural distribution, 24 from donations of public and private institutions, 91 from commercial nurseries and 58 acquired from BGV-CU collection management. Here we provide a record of collections, activities concerns and current strategies for documentation, conservation, characterisation, and management of the collection as important tools for researchers with interest in these valuable genetic resources.
Keywords: PHYLOGENY; [SPI.GPROC] Engineering Sciences [physics]/Chemical and Process Engineering; Plant Science; SATIVUS; phylogeny; sativus; Database; Ex situ conservation; [SDV.IDA]Life Sciences [q-bio]/Food engineering; Genetics; Genetic resources, Database, Crop diversity; [SPI.GPROC]Engineering Sciences [physics]/Chemical and Process Engineering; iridaceae; Genetic resources; Ecology, Evolution, Behavior and Systematics; BIOLOGIA VEGETAL; IRIDACEAE; Science & Technology; Plant Sciences; Agriculture; [SDV.IDA] Life Sciences [q-bio]/Food engineering; Agronomy; Crop diversity; FISIOLOGIA VEGETAL; Life Sciences & Biomedicine; Agronomy and Crop Science; 2. Zero hunger; 15. Life on land